IMPLEMENTASI JARINGAN INFORMASI KEARSIPAN NASIONAL UPAYA PENINGKATAN AKSES INFORMASI ARSIP NEGARA YANG AUTENTIK DAN BERKELANJUTAN - Kasman, Andi; Qoriah, Qoriah; Destrian, Ope; Zainuddin, Zhahirah Indrawati; Adnans, Abdhy Aulia (Universitas Padjadjaran, 2025)
Penelitian ini menganalisis implementasi Jaringan Informasi Kearsipan Nasional (JIKN) oleh Arsip Nasional Republik Indonesia (ANRI), berdasarkan Peraturan ANRI No. 17 Tahun 2021 dan Peraturan Kepala ANRI No. 22 Tahun 2011. Kedua regulasi tersebut menjadi landasan dalam perumusan standar layanan dan strategi penyediaan informasi kearsipan arsip negara yang autentik dan berkelanjutan. Penelitian ini menggunakan metode kualitatif deskriptif dengan teknik purposive sampling melalui observasi, studi pustaka, serta analisis regulasi dan teori yang relevan. Teori Sistem digunakan sebagai kerangka analisis untuk mengevaluasi efektivitas JIKN sebagai suatu sistem jaringan yang menghubungkan berbagai lembaga kearsipan sebagai simpul. Hasil penelitian menunjukkan peningkatan jumlah simpul jaringan dan pengguna layanan informasi arsip autentik, serta penguatan koordinasi antara Pusat Jaringan Nasional dengan simpul-simpul daerah. Selain itu, penelitian menekankan pentingnya sinergi antarpemangku kepentingan, integrasi teknologi, dan harmonisasi kebijakan sebagai strategi utama dalam penguatan JIKN. Temuan ini menegaskan kontribusi JIKN dalam menyediakan layanan informasi kearsipan yang cepat, akurat, terjangkau, dan mendukung penguatan infrastruktur informasi nasional. This study examines the implementation of the National Archival Information Network (JIKN) by the National Archives of Indonesia (ANRI), guided by ANRI Regulation No. 17 of 2021 and Head of ANRI Regulation No. 22 of 2011. These regulations serve as the foundation for developing service standards and strategies to ensure authentic and sustainable archival information access. Employing a descriptive qualitative method with purposive sampling, the research uses observation, literature review, and regulatory analysis. System Theory frames the evaluation of how JIKN, as a network system, can function effectively through the integration of various archival institutions as nodes. The findings indicate a significant increase in the number of network nodes and users accessing authentic state archives, along with improved coordination between the National Network Center and its nodes. The study also highlights enhanced collaboration with stakeholders, technological integration, and policy alignment as critical strategies. These contribute to the development of accessible, accurate, fast, and cost-effective archival services, reinforcing the role of JIKN in supporting national information infrastructure.This study examines the implementation of the National Archival Information Network (JIKN) by the National Archives of Indonesia (ANRI), guided by ANRI Regulation No. 17 of 2021 and Head of ANRI Regulation No. 22 of 2011. These regulations serve as the foundation for developing service standards and strategies to ensure authentic and sustainable archival information access. Employing a descriptive qualitative method with purposive sampling, the research uses observation, literature review, and regulatory analysis. System Theory frames the evaluation of how JIKN, as a network system, can function effectively through the integration of various archival institutions as nodes. The findings indicate a significant increase in the number of network nodes and users accessing authentic state archives, along with improved coordination between the National Network Center and its nodes. The study also highlights enhanced collaboration with stakeholders, technological integration, and policy alignment as critical strategies. These contribute to the development of accessible, accurate, fast, and cost-effective archival services, reinforcing the role of JIKN in supporting national information infrastructure.